Eficiência de aplicação dos métodos de microscopia eletrônica no desenvolvimento de novas composições de construção civil na base de resíduos industriais e municipais - Goncalves, Alexandre Jose (2021)
Industrial activities generate waste that can be reused and transformed into reusable materials. Therefore, the main objective of the research was to demonstrate the efficiency of application of Scanning Electron Microscopy (SEM) methods and microanalysis methods coupled to SEM - Energy Dispersive Spectroscopy (EDS) with point analyses, areas and compositional mapping to increase efficiency scientific in the development of sustainable materials for civil construction, using different types of Industrial and Municipal Waste (RIM) as main raw materials. With these methods it is possible to explain the chemical and thermochemical interaction processes of the components helping to choose the percentage of the compositions to improve the interaction between industrial and municipal hazardous waste creating new ecologically correct civil construction composites with predetermined properties.